2020
DOI: 10.1002/hed.26341
|View full text |Cite
|
Sign up to set email alerts
|

Association of multimodal analgesia with perioperative safety and opioid use following head and neck microvascular reconstruction

Abstract: Background This study examines the association of multimodal analgesia (MMA) protocol for head and neck microvascular reconstruction with postoperative safety and opioid use. Methods Retrospective, intention‐to‐treat analysis of 226 patients undergoing head and neck microvascular reconstruction between January 1, 2014 and August 30, 2018 at a tertiary‐care hospital following MMA protocol implementation. Multivariable models examined outcomes of interest. Results There were no differences between groups in freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…Surgical outcomes are as follows: flap dehiscence (MMA, 16.0% vs non-MMA, 13.0%; P = .78), complete flap failure rate (3.0% vs 3.4%; P = .87), return to operating room (16.4% vs 12.9%; P = .76), and bleeding event/hematoma (6.2% vs 7.4%; P = .85). In contrast, Sayal et al 19 reported reduced likelihood of partial flap failure with MMA use (odds ratio [OR], 0.18; 95% CI, 0.04-0.91). Medical complications, including gastrointestinal and cardiovascular issues, were nonsignificant between the 2 groups.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Surgical outcomes are as follows: flap dehiscence (MMA, 16.0% vs non-MMA, 13.0%; P = .78), complete flap failure rate (3.0% vs 3.4%; P = .87), return to operating room (16.4% vs 12.9%; P = .76), and bleeding event/hematoma (6.2% vs 7.4%; P = .85). In contrast, Sayal et al 19 reported reduced likelihood of partial flap failure with MMA use (odds ratio [OR], 0.18; 95% CI, 0.04-0.91). Medical complications, including gastrointestinal and cardiovascular issues, were nonsignificant between the 2 groups.…”
Section: Resultsmentioning
confidence: 97%
“…Nine of 10 studies 16-24 (n = 1151) used an 11-point numerical scale to assess pain, including the visual analog scale (VAS) (6 studies, 16,20-24 n = 774) and the Defense & Veterans Pain Rating Scale (DVPRS) (1 study, 17 n = 65) ( Table 4 ). There was wide variation in subjective pain outcomes among the included studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations